Proposed Method to Generated Strong Keys by Fuzzy Extractor And Biometric - Saleem, Huda; Albermany, Huda; Hadi, Husein (International Journal of Engineering and Technology, 2018)
The typical scheme used to generated cryptographic key is a fuzzy extractor. The fuzzy extractor is the extraction of a stable data from biometric data or noisy data based on the error correction code (ECC) method. Forward error correction includes two ways are blocked and convolutional coding used for error control coding. â€œBose_Chaudhuri_Hocquenghemâ€ (BCH) is one of the error correcting codes employ to correct errors in noise data. In this paper use fuzzy extractor scheme to find strong key based on BCH coding, face recognition data used SVD method and hash function. Hash_512 converted a string with variable length into a string of fixed length, it aims to protect information against the threat of repudiation.Â Â